2016
DOI: 10.1080/19475705.2016.1271833
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of land use in landslide affected areas along the Łososina Dolna Commune, the Outer Carpathians, Poland

Abstract: Land use of landslides is still a poorly investigated problem. Landslides cannot be regarded as areas unsuitable for use since they occupy a significantly large surface. The ºososina Dolna municipality in the Outer Carpathians is characterized by a very large number of landslides (16% of the total area, about 500 landslides). Land-cover analysis of this agricultural and forest municipality showed a relatively similar structure of land-cover types on areas affected and unaffected by landslides. Six categories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(26 reference statements)
0
10
0
2
Order By: Relevance
“…The study area was located in the central part of the Outer Carpathians (in the Małopolskie municipality, Poland), close to Rożnów Lake (Figure 1), and covered latitudes 49 • 43 N to 49 • 46 N and longitudes 20 • 38 E to 20 • 43 E. Most of the study area consisted of agricultural land (42%), while forests accounted for 34% of the total area [22]. Despite the existence of landslides and landslide-prone areas, the affected areas were still extensively used for economic purposes [22]. The broad analysis of landslide density in various land use classes for the presented study area can be found in Kroh [22].…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The study area was located in the central part of the Outer Carpathians (in the Małopolskie municipality, Poland), close to Rożnów Lake (Figure 1), and covered latitudes 49 • 43 N to 49 • 46 N and longitudes 20 • 38 E to 20 • 43 E. Most of the study area consisted of agricultural land (42%), while forests accounted for 34% of the total area [22]. Despite the existence of landslides and landslide-prone areas, the affected areas were still extensively used for economic purposes [22]. The broad analysis of landslide density in various land use classes for the presented study area can be found in Kroh [22].…”
Section: Study Areamentioning
confidence: 99%
“…Despite the existence of landslides and landslide-prone areas, the affected areas were still extensively used for economic purposes [22]. The broad analysis of landslide density in various land use classes for the presented study area can be found in Kroh [22]. Landslide identification is challenging due to extensive land management, in the form of farmland, grasslands, and pasture, and continuous development of constructions in this area ( Figure 2).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…They usually occur on slopes above rivers and creeks. Following the updated Varnes classification (Hungr et al 2014), the landslides investigated are of types 11, 12, and 14-on clay/silt rotational, planar, and compound slides (Kroh 2016). Fieldwork identifying and mapping landslides using the framework of the SOPO system were Original Paper Landslides 15 & (2018)performed from October 2010 to June 2011 .…”
Section: Datamentioning
confidence: 99%